(untitled) (Journal of Environmental Science and Natural Resources, 2019)
Water samples were collected from the Rupsha river of Khulna region to determine ionic contamination for irrigation purpose. The chemical analyses included pH, EC, TDS and ions. pH values of water samples were slightly alkaline in nature. Samples were rated as fresh water based on TDS values. Samples were high salinity and low alkalinity hazards expressing C3S1. Regarding SAR and SSP values, samples were excellent and good classes, respectively. Samples were free from RSC and were very hard class. Regarding PI values, samples were under class-II implying 75% maximum soil permeability. Ca, Mg, Na, Cu, Ni, Zn, HCO3, SO4 and PO4 levels in samples were within safe limit. Cd, Cr and Cl ions in water samples were above the permissible limit and were treated as water contaminants for irrigation. From the present findings, it is noted that the detected ions as water contaminants should be considered for irrigation usage toward food safety. J. Environ. Sci. & Natural Resources, 11(1-2): 145-151 2018